A RANCANG BANGUN KEILMUAN PERBANKAN SYARI’AH STAIMAFA - Ahmad Dimyati (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
The debate on the Islamic Economics or Shariah Economics which have been dominated by three streams viz. the secularists, theologists, and integralists, have impacts on the scientific paradigm in various High Schools offering the relevant departments, including STAIMAFA without any exception. Based on this reality, a new scientific model is required to provide a middle approach without leaving the local context. The result shows that in the Islamic banking course in STAIMAFA which is based on pesantren value​​-based research, the scientific model approach applied is by using the stratified level of analysis model. This method is a way to integrate the differences in the academic tradition in the pesantren and the modern studies that integrate between the systematic and critical method of analysis.